THE ROLE OF COLLABORATIVE GOVERNANCE IN SUBANG’S SMART CITY DEVELOPMENT - Andani, Diah; Sri Dinarwati (Program Magister Ilmu Administrasi dan Kebijakan Publik, Pascasarjana, Universitas Pasundan, 2026)
The rapid development of digital transformation in the public sector has encouraged local governments in Indonesia to adopt more collaborative, adaptive, and technology-based governance models. Subang Regency, which is undergoing significant regional transformation due to the development of Patimban Seaport and its integration into the Rebana Metropolitan area, faces increasing demands to modernize its public service systems through smart city initiatives. This study examines the role of collaborative governance in advancing the smart city agenda in Subang Regency. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis involving government agencies, private sector representatives, academics, and community groups. The findings reveal that smart city development in Subang remains at a transitional stage and has not yet achieved the level of cross-sector integration required for effective implementation. Several constraints were identified, including sectoral ego among government agencies, uneven digital capacity of civil servants, limited data interoperability, and insufficient involvement of non-government actors. Analysis using collaborative governance theory indicates that initial conditions, institutional design, facilitative leadership, and collaborative processes have not been optimally developed, resulting in weak shared motivation and limited capacity for joint action. Nevertheless, opportunities exist to strengthen collaborative governance through improved institutional platforms, leadership development, enhanced digital literacy, and strategic partnerships with private and academic stakeholders. This study contributes to the understanding of how collaborative governance shapes digital transformation in local government contexts and offers practical recommendations for strengthening smart city implementation in Subang Regency. By reinforcing collaborative mechanisms, Subang has the potential to accelerate its smart city development and achieve more integrated, inclusive, and sustainable digital governance. Keyword : Collaborative governance, smart city.